Speak Up, Stand Out: Improving Self-Confidence through Public Speaking Training for Psychology Students - Cindy Anastasia; Alexandra Beatrix; Tiara Kusumadewi; Hana Safira; Khanza Nazala; Winda Wijaya; Carissa Aryella; Eka Danta Jaya Ginting (Lembaga Yasin AlSys, 2026)
Although public speaking and self-confidence have been widely examined, limited studies have addressed integrated training modules designed specifically for first-year psychology students in Indonesia. This study aims to develop and describe a training module to enhance self-confidence and public speaking skills among first-year students, Class of 2025, at the Faculty of Psychology, Universitas Sumatera Utara. A qualitative descriptive design for module development was employed, involving 15 participants selected purposively based on the results of a Training Needs Analysis. Data were collected through focus group discussions, questionnaires, pre- and post-tests, behavioural observation checklists, and trainer evaluations, and were analyzed descriptively. The findings show that many participants experienced psychological barriers to verbal participation, including fear of making mistakes (66.7%), shame in front of peers (20%), and low self-confidence (46.7%). A structured one-day training module consisting of material sessions, ice-breaking activities, and a public speaking practice activity titled “Just One Minute” was developed to address these barriers. Post-training measures and behavioural observations indicated improvements in students’ willingness to speak and reductions in communication anxiety. The study concludes that experiential learning and interactive training methods can support the development of speaking courage and reduce classroom communication anxiety among first-year university students. This study contributes to psychological intervention and academic communication training by identifying common speaking barriers among early-adult students and offering a practical module for strengthening self-confidence and public speaking skills. The module may serve as a reference for psychology faculties and other educational institutions in designing structured communication-skill programmes, while further research is recommended to examine its long-term effects on academic participation and self-efficacy.